Distribution of cfr in Staphylococcus spp. and Escherichia coli Strains from Pig Farms in China and Characterization of a Novel cfr-Carrying F43:A-:B- Plasmid - Liu, Xiao-Qin; Wang, Jing; Li, Wei; Zhao, Li-Qing; Lu, Yan; Liu, Jian-Hua; Zeng, Zhen-Ling (Frontiers in Microbiology, 2017)
The multiresistance gene cfr is widely distributed among various gram-positive and gram-negative species in livestock in China. To better understand the epidemiology of cfr among Staphylococcus and E. coli isolates, 254 Staphylococcus and 398 E. coli strains collected from six swine farms in China were subjected to prevalence and genetic analysis. Forty (15.7%) Staphylococcus isolates, including 38 Staphylococcus sciuri strains, one Staphylococcus chromogenes strain, and one Staphylococcus lentus strain, and two (0.5%) E. coli isolates were found to contain the cfr gene. Most of the 38 S. sciuri strains were clonally unrelated; however, clonal dissemination of cfr-positive S. sciuri was detected at the same farm. In eight randomly selected cfr-positive staphylococci, a cfr-harboring module (IS21-558-cfr-ΔtnpB) was detected in six S. sciuri isolates; cfr was bracketed by two copies of ISEnfa4 or IS256 in the remaining two S. sciuri isolates. In the two E. coli isolates, EP25 and EP28, cfr was flanked by two IS26 elements in the same or opposite orientation, respectively. Complete sequence analysis of the novel F43: A-: B- plasmid pHNEP28 revealed that it contains two multi-resistance regions: cfr together with floR, qnrS1 interspersed with IS26, △ISCR2 and ISKpn19, and blaTEM-1 together with tet(M) interspersed with IS26, ISApl1, △Tn2, and △IS1B. The coexistence of cfr with other resistance genes on a conjugative plasmid may contribute to the dissemination of these genes by co-selection. Thus, rational drug use and continued surveillance of cfr in swine farms are warranted.